Processing of Dried Yogurt (KISIIK) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT: The research was conducted to study the production of dried yogurt {kishk) using cabinet. oven, sun drying and storage at room temperature during 12 weeks. This result showed that kishk cabinet dried had water content 6,73%. protein 11,53%, ash 5,54%, pH value 4,00. Titratable acidity 1.04% lactic acid, and total microorganism 0.5 x 10 colonyiguun. Kishk oven dried had water content 9.15%, piritein 11,30%. ash 5.56%_ pi! value 4 ,06, titralable acidity 1.10% lactic acid, and no microorganisms detected until li weeks. Kislik sun dried had water content 9.47%, protein 10.31%, p11 value 4.02, taratable acidity 1,10% lactic acid and total microorganism 4.0 x 104 colony/gram. During storage 12 weeks at room tcmperatur water content. protein, pit value. and total microorganism kishk cabinet dried, own and kishk sun dried decreased However there appears ability to produce kishk will' cabinet, oven. and sun drvnig.